Ženske in industrija na Balkanu - Vodopivec, Nina (Glasnik Slovenskega etnološkega društva, 2023)
The article was inspired by Chiara Bonfiglioli’s book on the experience of socialist industrial modernisation in Yugoslavia and deindustrialisation in the selected states after the collapse of the state. First, the theoretical background, the central concepts of the book and the rich empirical material on women textile workers are presented, which is critically compared with the research material collected by the author of the article among textile workers in Slovenia over the last 20 years. The aim is to draw attention to the lack of such research in Slovenia and encourage further studies on industrial workers and work.
Keywords: deindustrializacija; industrija; Jugoslavija; socializem; ženske